Deterring Corruption and Improving Governance in Road Construction and Maintenance - World Bank (Washington, DC, 2014)
This sourcebook is part of a broader program on governance and corruption in the transport sector. The Sourcebook is meant as a resource to sector practitioners to assess the extent and risks of corruption in the sector and to improve governance in ways that reduce corruption. As this is an emerging field, the sourcebook is not intended to be a manual, nor a set of directives but rather to organize and illustrate approaches and tools which sector practitioners may find useful. This sourcebook is in seven sections. Section two provides an overview of governance and corruption, and the framework used to evaluate governance and corruption risks in transport. Section three describes a 'generic' transport sector structure and several tools for evaluating governance at the sector level. The next four sections describe how to detect corruption, and improve governance in: sector policy and planning (section four); capital works (section five); government engineering and construction units (section six); and public-private partnerships (section seven).